STUDY OF CONTEMPORARY METHODS OF ENTERPRISE MANAGEMENT - Jalilov Arslon Khoshimovich; Jumayev Navruzbek Fakhriddin ugli; Ismoilova Aziza Akmal kizi (Modern American Journals, 2025)
This article analyzes the leading approaches to modern enterprise management, principles of innovative management, and management technologies that serve to increase efficiency in today's highly competitive environment. Methods such as digital management, data-based decision-making, new ideas of management, customer-centric management, and lean management aimed at unlocking the potential of employees are highlighted as the main factors determining the stability of today's enterprises. The article presents practical conclusions on the automation of business processes, modernization of leadership strategies, and the formation of an organizational model that is quickly adaptable to changing market requirements. The scientific significance of the study is that it offers a comprehensive approach to the development strategy of enterprises, combining traditional approaches to management with modern innovative methods.
Keywords: Innovative management, strategy, CPM, benchmarking, Henri Fayol, kaizen, Toyota.